2021
DOI: 10.1111/csp2.374
|View full text |Cite
|
Sign up to set email alerts
|

Principles for the socially responsible use of conservation monitoring technology and data

Abstract: Wildlife conservation and research benefits enormously from automated and interconnected monitoring tools. Some of these tools, such as drones, remote cameras, and social media, can collect data on humans, either accidentally or deliberately. They can therefore be thought of as conservation surveillance technologies (CSTs). There is increasing evidence that CSTs, and the data they yield, can have both positive and negative impacts on people, raising ethical questions about how to use them responsibly. CST use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…As a note of caution, emerging technologies and conservation culturomics approaches should be used in full respect of human rights and carefully consider ethical guidelines and data privacy and protection concerns [79,84].…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…As a note of caution, emerging technologies and conservation culturomics approaches should be used in full respect of human rights and carefully consider ethical guidelines and data privacy and protection concerns [79,84].…”
Section: Trends In Ecology and Evolutionmentioning
confidence: 99%
“…In addition to the improvement in processing efficiency, we demonstrated that MegaDetector facilitates the blurring of human images prior to data processing. The human ethics of camera trapping has received attention recently (Sandbrook et al, 2021; Sharma et al, 2020) and the ability to anonymize images before they are viewed by human observers or archived is in our opinion considered best practice. To this end, we provide a script (https://github.com/WildCoLab/WildCo-FaceBlur) which takes the human-labelled objects identified by MegaDetector and blurs them using Python via a simple R interface, which is familiar for many ecologists.…”
Section: Discussionmentioning
confidence: 99%
“…With many mid-to-large scale projects amassing millions of photos and reaching terabytes of data in less than a year, the time committed to processing these data becomes increasingly unmanageable, ballooning time and monetary budgets. This issue is particularly prominent in recreation ecology studies, where the number of human images captured may frequently be in the millions, with the additional concern of respecting human privacy adding complexity to the issue (Sandbrook et al, 2018(Sandbrook et al, , 2021. In some cases, these ethical concerns lead to deletion of all human images, reducing the possibility for detailed assessment of humanwildlife interactions (Naidoo and Burton, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid alienating the very communities we wish to work with, we recommend carefully attending to covert expressions of community resistance, such as gossip and rumor that can subtly, but thoroughly, undermine conservation activities. Communication regarding scientific activities such as camera trap surveys must be conducted ethically and local people included in the survey design (Sandbrook et al, 2021) to avoid incorrect information being spread about the cameras' presence in the communities concerned. For example, chimpanzee conservationists in Sierra Leone were forced to temporarily stop camera trapping due to the concerns of some community groups.…”
Section: Implications For Primate Conservation Practicementioning
confidence: 99%